Setting the tone: crossmodal emotional face-voice combinations in continuous flash suppression - Müller, Ulrich W. D.; Gerdes, Antje B. M.; Alpers, Georg W. (Frontiers in Psychology, 2025)
Emotional stimuli are preferentially processed in the visual system, in particular, fearful faces. Evidence comes from unimodal studies with emotional faces, although real-life emotional encounters typically involve input from multiple sensory channels, such as a face paired with a voice. Therefore, in this study, we investigated how emotional voices influence preferential processing of co-occurring emotional faces. To investigate early visual processing, we used the breaking continuous flash suppression paradigm (b-CFS): We presented fearful, happy, or neutral faces to one eye, which were initially inaccessible to conscious awareness due to the predominant perception of a dynamic mask presented to the other eye. Faces were presented either unimodally or paired with non-linguistic vocalizations (fearful, happy, neutral). Thirty-six healthy participants were asked to respond as soon as the faces reached conscious awareness. We replicated earlier findings that fearful faces broke suppression faster overall, supporting a threat bias. Moreover, all faces broke suppression faster when paired with voices. Interestingly, faces paired with neutral and happy voices broke suppression the fastest, followed by faces with fearful voices. Thus, in addition to supporting a threat bias in unimodally presented fearful faces, we found evidence for crossmodal facilitation.